Distibanes and Distibenes from Reduction of Sb(NONR)Cl by using MgI Reagents. Issue 62 (9th October 2019) - Schwamm, Ryan J.; Coles, Martyn P.
Abstract: The bis(amidodimethyl)disiloxane antimony chlorides Sb(NON R )Cl (NON R =[O(SiMe2 NR)2 ] 2− ; R= t Bu, Ph, 2, 6‐Me2 C6 H3 =Dmp, 2, 6‐ i Pr2 C6 H3 =Dipp, 2, 6‐(CHPh2 )2 ‐4‐ t BuC6 H2 = t Bu‐Bhp) are reduced to Sb II and Sb I species by using Mg I reagents, [Mg(BDI R′ )]2 (BDI=[HCC(Me)NR′2 ] − ; R′=2, 4, 6‐Me3 C6 H2 =Mes, Dipp). Stoichiometric reactions with Sb(NON R )Cl (R= t Bu, Ph) form dimeric Sb II stibanes [Sb(NON R )]2, shown crystallographically to contain Sb−Sb single bonds. The analogous distibane with R=Dmp substituents has an exceptionally long Sb−Sb interaction and exhibits spectroscopic and reactivity properties consistent with radical character in solution. When R=Dipp, reductions with Mg I reagents directly give distibenes [Sb( μ ‐NON Dipp )Mg(BDI R′ )(THF) n ]2 (R′=Mes, n =1; R′=Dipp, n =0). Crystallographic analysis shows a trans ‐substitution of the Sb=Sb double bond, with bridging NON Dipp ‐ligands between the Sb I and Mg II centres. An attempt to access the NON Ph ‐analogue using the same protocol afforded the polystibide cluster Sb8 [ μ 4, η 2:2:2:2 ‐Mg(BDI Mes )]4, which co‐crystallized with the ligand transfer product, [Mg(BDI Mes )]2 ( μ ‐NON Ph ). Abstract : Reduction of antimony(III) chloride species with Mg I reagents affords Sb II or Sb I compounds, depending on the substituents present on the supporting ligand. The distibene compounds retain a magnesium centre, linked to the Sb=Sb unit through a bridging ligand (see figure).